I am being asked to prove that $$\sum\limits_{k=0}^{n}\cos(kx)=\frac{1}{2}+\frac{\sin(\frac{2n+1}{2}x)}{2\sin(x/2)}$$

I have some progress made, but I am stuck and could use some help.

What I did:

It holds that $$\sum\limits_{k=0}^{n}\cos(kx)=\sum\limits_{k=0}^{n}Re(\cos(kx))=\sum\limits_{k=0}^{n}Re(\cos(x)^{k})=Re(\sum\limits_{k=0}^{n}\cos(x)^{k})=Re\left(\cos(0)\cdot\frac{\cos(x)^{n}-1}{\cos(x)-1}\right)=Re\left(\frac{\cos(x)^{n}-1}{\cos(x)-1}\right) $$

For any $z_{1},z_{2}\in\mathbb{C}$ we have it that if $z_{1}=a+bi,z_{2}=c+di$ then $$\frac{z_{1}}{z_{2}}=\frac{z_{1}\overline{z2}}{|z_{2}|^{2}}=\frac{(a+bi)(c-di)}{|z_{2}|^{2}}=\frac{ac-bd+i(bc-ad)}{|z_{2}|^{2}}$$ hence $$Re\left(\frac{z_{1}}{z_{2}}\right)=\frac{Re(z_{1})Re(z_{2})-Im(z_{1})Im(z_{2})}{|z_{2}|^{2}}$$

Thus, $$Re\left(\frac{\cos(x)^{n}-1}{\cos(x)-1}\right)=\frac{(\cos(nx)-1)(\cos(x)-1)-\sin(nx)\sin(x)}{(\cos(x)-1)^{2}+\sin^{2}(x)}=\frac{\cos(nx)\cos(x)-\cos(nx)-\cos(x)+1-\sin(nx)\sin(x)}{\cos^{2}(x)-2\cos(x)+1+\sin^{2}(x)}=\frac{\cos(nx)\cos(x)-\cos(nx)-\cos(x)+1-\sin(nx)\sin(x)}{-2\cos(x)+2}=\frac{\cos(nx)\cos(x)-\cos(nx)-\cos(x)+1-\sin(nx)\sin(x)}{-2(\cos(x)-1)}= \frac{=\cos(nx)\cos(x)-\cos(nx)-\cos(x)+1-\sin(nx)\sin(x)}{-2(-2\cdot\sin^{2}(x/2))}=\frac{\cos(nx)\cos(x)-\cos(nx)-\cos(x)+1-\sin(nx)\sin(x)}{4\sin^{2}(x/2)}=\frac{\cos(nx)\cos(x)-\cos(nx)-\cos(x)+1-\sin(nx)\sin(x)}{4\sin^{2}(x/2)}=\frac{\cos(x(n+1))-\cos(nx)-\cos(x)+1}{4\sin^{2}(x/2)} $$

This is the part where I am stuck, I would appriciate any help or hint on how to continue.

Edit: Given the corrections by André I get:


so $$\cos(nx+x)\cos(x)+\sin(nx+x)\sin(x)=\cos(xn+x-x)-\cos(nx)=0$$

Edit 2: I found anoter mistake in the above, I will try to correct

Edit 3: When multiplying correctly the above it works out :-)


There are faster ways to go, but if you want to continue along the path you have taken, you are quite close to the end. Please see the remark for a couple of small things that need to be corrected in the calculation. Essentially the same trigonometric tricks continue to work.

By a double angle formula for the cosine, we have $$\cos x=1-2\sin^2(x/2),$$ so $$\frac{1-\cos x}{4\sin^2(x/2)}=\frac{1}{2},$$ part of what you are aiming for. However, this could have been obtained in a simpler way in the third displayed formula after the "Thus," in the OP.

And the front part will "simplify" by a difference of $\cos$ formula, obtained from $$\cos(a+b)=\cos a\cos b-\sin a\sin b,\qquad \cos(a-b)=\cos a\cos b+\sin a\sin b.$$ Subtract. We get $$\cos(a+b)-\cos(a-b)=-2\sin a\sin b.$$ Let $a+b=x(n+1)$, and $a-b=nx$. So $a=\dfrac{x(2n+1)}{2}$ and $b=\dfrac{x}{2}$.

Remark: There is a little sign glitch in the calculation of $(a+bi)(c-di)$. Note that the real part should be $ac+bd$. Also, when you are summing the geometric progression, we need $\text{cis}^{n+1}$.

  • $\begingroup$ I am having a little problem with this, I get the answer with a minus sign. can you please help me with telling me where I did wrong ? $\cos(x(n+1))-\cos(nx)=-2\sin(xn+\frac{x}{2})\sin(\frac{x}{2})$ thus $\frac{\cos(x(n+1))-\cos(nx)}{4\sin^{2}(x/2)}=\frac{-2\sin(xn+\frac{x}{2})\sin(\frac{x}{2})}{4\sin^{2}(x/2)}=-\frac{\sin(xn+\frac{x}{2})}{2\sin(\frac{x}{2})}$ $\endgroup$ – Belgi Oct 31 '12 at 10:09
  • $\begingroup$ Am I doing the last step wrong or do you think I have a previous minus sign error somewhere ? $\endgroup$ – Belgi Oct 31 '12 at 10:17
  • $\begingroup$ I corrected that error after you last comment, but its still not working right: $(\cos(nx)-1)(\cos(x)-1)+\sin(nx)\sin(x)=\cos(nx)\cos(x)-\cos(nx)-\cos(x)+1+\sin(nx)\sin(x)$ so $\cos(nx)\cos(x)+\sin(nx)\sin(x)=\cos(xn-x)-\cos(nx)=\cos(x(n-1))-\cos(nx)$. If $a+b=xn-x,a-b=xn$ then $a=xn-\frac{x}{2},b=-\frac{x}{2}$ so $-2\sin(a)\sin(b)=-2\sin(x(n-1))\sin(-\frac{x}{2})=+2\sin(x(n-1))\sin(\frac{x}{2})$. So when $\sin(\frac{x}{2})$ cancels out we get $\frac{\sin(x(n-1))}{2\sin(\frac{x}{2})}$ $\endgroup$ – Belgi Oct 31 '12 at 10:38
  • $\begingroup$ I'll try to correct the second mistake you found, thanks! $\endgroup$ – Belgi Oct 31 '12 at 10:39
  • $\begingroup$ I still have a problem after your last correction: $(\cos(nx+x)-1)(\cos(x)-1)+\sin(nx+x)\sin(x)=\cos(nx+x)\cos(x)-\cos(nx)-\cos(x)+1+\sin(nx+x)\sin(x)$ so $\cos(nx+x)\cos(x)+\sin(nx+x)\sin(x)=\cos(xn+x-x)-\cos(nx)=0$ $\endgroup$ – Belgi Oct 31 '12 at 10:44

$$\sum_{0\le r\le n}e^{ikx}=\frac{e^{i(n+1)x}-1}{e^{ix}-1}$$

$$=\frac{e^{\frac{i(n+1)x}2}}{e^{\frac{ix}2}}\frac{\left(e^{\frac{i(n+1)x}2}-e^{-\frac{i(n+1)x}2}\right)}{\left( e^{\frac{ix}2}-e^{-\frac{ix}2}\right)}$$

$$=e^{\frac{inx}2}\frac{2i\sin\frac{(n+1)x}2}{2i\sin{\frac{x}2}}$$ as $e^{iy}-e^{-iy}=2i\sin y,$

$$=(\cos\frac{nx}2+i\sin\frac{nx}2)\frac{\sin\frac{(n+1)x}2}{\sin{\frac{x}2}}$$ using Euler's identity.

Its real part is $$\cos\frac{nx}2 \frac{\sin\frac{(n+1)x}2}{\sin{\frac{x}2}}=\frac{2\cos\frac{nx}2\sin\frac{(n+1)x}2}{2\sin{\frac{x}2}}=\frac{\sin\frac{(2n+1)x}2+\sin{\frac{x}2}}{2\sin{\frac{x}2}}$$ using $2\sin A\cos B=\sin(A+B)+\sin(A-B)$

  • $\begingroup$ Can you please provide some insight on how did you know to factor the denomenator numerator in that way in the second line ? $\endgroup$ – Belgi Oct 31 '12 at 10:56
  • $\begingroup$ @Belgi, we know $e^{2y}-1=e^y(e^y-e^{-y})$ and my target was to utilize $e^{iy}-e^{-iy}=2i\sin y$. You may have a look into the last approach of math.stackexchange.com/questions/183859/… $\endgroup$ – lab bhattacharjee Oct 31 '12 at 11:10

Just multiply both sides by $2\sin(x/2)$ and use Briggs' formula: $$ 2 \sin(x/2)\cos(kx) = \sin((k+1/2)x)-\sin((k-1/2)x)$$ to get a telescoping sum.

  • $\begingroup$ Isn't there a nice way to continue my work ? $\endgroup$ – Belgi Oct 31 '12 at 9:18
  • $\begingroup$ Why did you take with a sin(x/2)? $\endgroup$ – Buraian Oct 4 '20 at 10:53

Here is the simplest way I've found. \begin{align} 1+2\sum_{k=1}^ncos(\theta) & = \sum_{k=-n}^n e^{ik\theta} \\ & = \frac{e^{i(n+1/2)\theta}-e^{-i(n-1/2)\theta}}{e^{i\theta /2}-e^{-i\theta / 2}} \\ & =\frac{\sin(n+1/2)\theta}{\sin(\theta/2)} \\ \end{align} which can easily be rearranged to get the desired identity. See https://en.wikipedia.org/wiki/List_of_trigonometric_identities#Lagrange's_trigonometric_identities


$\require{cancel}$ Start by being inspired by the product-to-sum identity: $$ 2 \cos a \sin b = \sin(a+b) - \sin(a-b) , $$

then naturally let $a = kx$, next, in order for the right-hand side terms to be eliminated when multiple equalities are superimposedly added, which eventually making the remaining terms as few as possible, the value of $((a+b)-(a-b))$ should be the smallest integer multiple of $x$, hence let $b=\dfrac{x}{2} ,$ so the equality changes as $$ 2 \cos kx \sin\dfrac{x}{2} = \sin\left(k+\dfrac{1}{2}\right)x - \sin\left(k-\dfrac{1}{2}\right)x . $$

And then, use a table to visualize the cumulative destructive process of the right-hand side terms: $$\begin{array}{c|cc} +)\ k+\dfrac{1}{2} & \cancel{\dfrac{3}{2}} & \cancel{\dfrac{5}{2}} & \cancel{\dfrac{7}{2}} & \cdots & \cancel{n-\dfrac{1}{2}} & n+\dfrac{1}{2}\\ \hline -)\ k-\dfrac{1}{2} & \dfrac{1}{2} & \cancel{\dfrac{3}{2}} & \cancel{\dfrac{5}{2}} & \cdots & \cancel{n-\dfrac{3}{2}} & \cancel{n-\dfrac{1}{2}} \end{array} \\ ⇓ \\ \sum_{k=1}^n \left[\sin\left(k+\dfrac{1}{2}\right)x - \sin\left(k-\dfrac{1}{2}\right)x\right] = \sin\left(n+\dfrac{1}{2}\right)x - \sin\dfrac{x}{2} . $$

Thus $$ \sum_{k=1}^n \cos kx = \left.\left[\sin\left(n+\dfrac{1}{2}\right)x - \sin\dfrac{x}{2}\right] \middle/ \left(2 \sin\dfrac{x}{2}\right)\right. . $$

P.S. Similarly, $$\sum_{k=1}^n \sin kx = \left.\left[\cos\dfrac{x}{2} - \cos\left(n+\dfrac{1}{2}\right)x\right] \middle/ \left(2 \sin\dfrac{x}{2}\right)\right.$$ can be derived from $2 \sin a \sin b = \cos(a-b) - \cos(a+b)$ through the same steps.

  • $\begingroup$ table to visualize very useful $\endgroup$ – onepound Feb 5 '20 at 12:24

$$\begin{align} \sum_{k=0}^n2\cos k\theta&=\sum_{k=0}^n(e^{i\theta k}+e^{-i\theta k})\\ &=\frac{e^{i\theta(n+1)}-1}{e^{i\theta}-1}+\frac{e^{-i\theta(n+1)}-1}{e^{-i\theta}-1}\\ &=\frac{e^{in\theta}+e^{-in\theta}-e^{i(n+1)\theta}-e^{-i(n+1)\theta}-e^{i\theta}-e^{-i\theta}+2}{2-e^{i\theta}-e^{-i\theta}}\\ &=\frac{2\cos n\theta-2\cos(n+1)\theta+2-2\cos\theta}{2-2\cos\theta}\\ &=\frac{\cos n\theta-\cos(n+1)\theta+1-\cos\theta}{1-\cos\theta}=\frac{\sin(n+\frac 1 2)\theta}{\sin\frac\theta2}+1 \end{align}$$


We wish the compute the sum $$S=\sum_{k=0}^n \cos(k\theta)$$ We can use the properties of the Chebyshev polynomials of the first kind. Recall that the $n$th Chebyshev polynomial $T_n$ satisfies the relation $$T_n(\cos\theta)=\cos(n\theta).$$ With this definition your sum can be restated as $$S=\sum_{k=0}^n T_k(\cos\theta)$$ We can let $\cos(\theta):=x$ and deduce that $$T_0=1 \text{ and }T_1(x)=x$$ And because of the following identity, $$\cos((n+1)\theta) + \cos((n-1)\theta) = 2\cos (\theta) \cos (n\theta)$$ Which can be proved via sum-difference formulas for cosine, we can again let $\cos(\theta):=x$ and shift our index to obtain $$T_{n+2}=2xT_{n+1}-T_n$$ So let's return to the sum $$g_n(x)=\sum_{k=0}^n T_k(x)$$ We can start by summing both sides of the recurrence relation: $$\sum_{k=0}^n T_{k+2}=2x\sum_{k=0}^nT_{k+1}-\sum_{k=0}^nT_k$$ We can mix and match different terms in the sums: $$g_n-T_0-T_1+T_{n+1}+T_{n+2}=2x(g_n-T_0+T_{n+1})-g_n$$ Some algebra, $$2(1-x)g_n=T_0-2xT_0+T_1-T_{n+1}+2xT_{n+1}-T_{n+2}$$ However, using the recurrence, one can notice $2xT_{n+1}-T_{n+2}=T_n.$ Furthermore, $T_0=1$ and $T_1=x$, as stated before. Thus, $$g_n(x)=\frac{1}{2}+\frac{T_n(x)-T_{n+1}(x)}{2(1-x)}$$ Letting $x=\cos(\theta)$, $$g_n(\cos\theta)=S=\frac{1}{2}+\frac{\cos(n\theta)-\cos((n+1)\theta)}{2(1-\cos\theta)}$$ It remains to be shown that $$\frac{\cos(n\theta)-\cos((n+1)\theta)}{1-\cos\theta}=\frac{\sin\left(\frac{2n+1}{2}x\right)}{\sin(x/2)}$$ Which I'm actually not sure how to verify, though I have checked it in Desmos and on Wolfram.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.